Effects of different doses of estradiol benzoate used in a cervical relaxation protocol on the success of non-surgical embryo recovery and luteal function in superovulated ewes - Dias, J. H.; Gonçalves, J. D. [UNESP]; Arrais, A. M.; Souza-Fabjan, J. M.G.; Bastos, R.; Batista, R. I.T.P.; Siqueira, L. G.B.; Oliveira, M. E.F. [UNESP]; Fonseca, J. F. (Elsevier, 2023)
This study investigated the effectiveness of different doses of estradiol benzoate (EB) to promote cervical relaxation and their effects on luteal function and outcomes of non-surgical embryo recovery (NSER) in sheep. Multiparous (MULT) and nulliparous (NULL) crossbred Lacaune X Santa Inês ewes were superovulated and naturally bred. Seven days after progesterone withdrawal, females were randomly assigned to one of three distinct cervical relaxation protocols, consisting of i.m. treatment with 37.5 µg d-cloprostenol and different doses of EB: 0.0 mg (0.0EB group; n = 3 NULL and 14 MULT); 0.5 mg (0.5EB group; n = 4 NULL and 12 MULT) or 1.0 mg (1.0EB group, n = 6 NULL and 11 MULT) 16 h before NSER. All ewes received 50 IU of oxytocin 20 min before NSER (D17). Blood samples were collected and ultrasound exams (B-mode and color Doppler) were performed at two timepoints: immediately before d-cloprostenol and EB treatments and prior to NSER. Estrous behavior, corpora lutea count and NSER success outcomes were not affected by EB treatments nor parity (P > 0.05). Embryo recovery rate was greater for ewes in the 0.5EB group and in the NULL ewes (P < 0.05). Ovarian biometrics differed between the two evaluation timepoints in all groups (P < 0.05). Plasma estradiol increased over time, reaching a significant greater level in 1.0EB ewes compared to controls on D17 (P < 0.05), whereas progesterone concentrations decreased over time in all groups (P > 0.05). In conclusion, treatments did not affect NSER success but they did affect luteal function by altering P4 and E2 concentrations. Therefore, the NSER technique can be successfully performed in ewes with or without prior treatment with EB.
Keywords: Cervical dilation; NSER; Progesterone; Sheep